The Effects of Deregulated Ribosomal Biogenesis in Cancer - Yiwei Lu; Shizhuo Wang; Yisheng Jiao (Biomolecules, 2023)
Ribosomes are macromolecular ribonucleoprotein complexes assembled from RNA and proteins. Functional ribosomes arise from the nucleolus, require ribosomal RNA processing and the coordinated assembly of ribosomal proteins (RPs), and are frequently hyperactivated to support the requirement for protein synthesis during the self-biosynthetic and metabolic activities of cancer cells. Studies have provided relevant information on targeted anticancer molecules involved in ribosome biogenesis (RiBi), as increased RiBi is characteristic of many types of cancer. The association between unlimited cell proliferation and alterations in specific steps of RiBi has been highlighted as a possible critical driver of tumorigenesis and metastasis. Thus, alterations in numerous regulators and actors involved in RiBi, particularly in cancer, significantly affect the rate and quality of protein synthesis and, ultimately, the transcriptome to generate the associated proteome. Alterations in RiBi in cancer cells activate nucleolar stress response-related pathways that play important roles in cancer-targeted interventions and immunotherapies. In this review, we focus on the association between alterations in RiBi and cancer. Emphasis is placed on RiBi deregulation and its secondary consequences, including changes in protein synthesis, loss of RPs, adaptive transcription and translation, nucleolar stress regulation, metabolic changes, and the impaired ribosome biogenesis checkpoint.